Metodologia współczesnego językoznawstwa rosyjskiego - Kamałowa, Ałła (Przegląd Rusycystyczny, 2009)
METHODOLOGY OF THE CONTEMPORARY RUSSIAN LINGUISTICS Summary In the late 20th century, the Russian linguistics has changed, especially with regard to research philosophy, methods applied and the subject of study. The anthropocentric paradigm in the language studies contributed to the emergence of various schools and, therefore, brought about a particular vagueness of terminology and alliances between linguistics and other scientifi c disciplines. However, the anthropocentric paradigm enriched linguistics with sophisticated techniques of study of various language phenomena; co-operation with other sciences brought out a new modus of speculation about language that is referred to as synergetic. The article points out that synergetics is highly applicable to the study of complex systems such as generative paradigms, semantic category etc. The author’s standpoint is that synergetics claims to become a new scientifi c paradigm that might aggregate a scientifi c, religious and esoteric understanding of language, human and universe. METODOLOGIA WSPÓŁCZESNEGO JĘZYKOZNAWSTWA ROSYJSKIEGO Streszczenie U schyłku XX w. rosyjskie językoznawstwo zmieniło się, zwłaszcza w odniesieniu do fi lozofi i i przedmiotu badań, a także stosowanych metod. Antropocentryczny paradygmat w badaniach językowych przyczynił się do powstania różnych szkół i dlatego też skutkował szczególnym rozmyciem terminologii oraz sojuszem językoznawstwa z innymi dyscyplinami naukowymi. Jednak antropocentryczny paradygmat wzbogacił językoznawstwo o wyszukane techniki badawcze różnych zjawisk językowych; współdziałanie z innymi naukami przyczyniło się do powstania nowego sposobu spekulacji o języku, który określa się jako synergetyczny. W artykule wykazano, że synergetyka ma szerokie zastosowanie przy badaniu złożonych systemów, takich jak paradygmaty generatywne, kategoria semantyczna itd. Autorka zajmuje stanowisko, że synergetyka ubiega się o miano nowego paradygmatu naukowego, który może scalić naukowe, religijne i ezoteryczne rozumienie języka, człowieka i świata.